The chemistry of heterocycles : nomenclature and chemistry of three to five membered heterocycles - Ram, Vishnu Ji; Sethi, Arun; Nath, Mahendra; Pratap, Ramen (Elsevier, 2017)
Heterocycles are ubiquitously present in nature and occupy a unique place in organic chemistry as they are part of the DNA and haemoglobin that make life possible. The Chemistry of Heterocycles covers an introduction to the topic, followed by a chapter on the nomenclature of all classes of isolated, fused and polycyclic heterocycles. The third chapter delineates the highly strained three membered N, O and S containing aromatic and non-aromatic heterocycles with one and more than one similar and dissimilar heteroatom. The four-membered heterocycles are abundantly present in various natural and synthetic products of pharmacological importance. This chapter describes the natural abundance, synthesis, chemical reactivity, structural features and their medicinal importance. This class of compounds are present as sub-structures in penicillin and cytotoxic Taxol. Lastly, a chapter on the natural abundance, synthesis, chemical reactivity and pharmacological importance of 5-membered heterocycles with N, O, S heteroatom is covered. The chemistry of heterocycles with mixed heteroatom such as, N-S, N-O, N-S etc. is also described.